Urban agriculture and the social role of urbanism: Planning and ethics for communities and territories - Marat-Mendes, Teresa; Cunha Borges, João (AESOP, 2019)
UN Habitat III and the 2030 Agenda for Sustainable Development have challenged scholars to reappraise the urban environment from the sustainability perspective. The study of urban form (urban morphology), as well as of resources and materials needed for cities to function (urban metabolism) are two specific areas which have potential to assess the urban environment and their projected development. Departing from such contributions this presentation, focus on the contributions of an ongoing research Project (SPLACH – Spatial Planning for Change), which aims to promote a sustainable urban transition of Lisbon Metropolitan Area (LMA), informed on a desirable food-based urbanism, with impact on the improvement of environmental conditions and people’s lives. LMA concentrates about 3 million inhabitants, whom mostly occupy its peripheral residential areas, mostly developed throughout 20th century. Many of these areas gave rise to relevant problems including social isolation and car dependency, while others have witnessed a number of municipal and private initiatives to counteract such issues, including the promotion of urban agriculture. SPLACH Project has surveyed a number of case studies which aim to theorize planning and housing dynamics occurred in LMA while identifying their impacts on territorializing ethical principles grounded on urban agriculture initiatives. Specifically, we will question what specific issues have been identified in SPLACH case studies which deem to provide opportunities to rethink urban planning and urban form towards a more sustainable environment and promote the social role of urban planning.
Keywords: urban agriculture; urban planning; ethics; Lisbon Metropolitan Area